Controlling Neuronal Activity. - Schneider, M. Bret; Gradinaru, Viviana; Zhang, Feng; Deisseroth, Karl (American Journal of Psychiatry, 2008)
The writers discuss a new technology, optogenetics, which makes it possible to turn neuronal activity on and off in distinct neuronal populations. They comment on the processes used in optogenetics and the application of the technology. The argue that current preclinical studies using optogenetics will aid understanding of the neuronal circuits involved in human disease.